Pengaruh Kesadaran Wajib Pajak dan Kepercayaan Wajib Pajak pada Pemerintah terhadap Kepatuhan Membayar Pajak Bumi dan Bangunan di Kecamatan Bulakamba - Rizqi Amellia; Roni, Roni; Nasiruddin, Nasiruddin; Dumadi, Dumadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze taxpayer awareness and trust in the government in encouraging compliance with the payment of Land and Building Tax (PBB) in the Bulakamba District. A quantitative method was used in this research, with data collection carried out through the distribution of questionnaires to 100 respondents who are PBB taxpayers in the area. The data analysis technique used is multiple linear regression with the help of SPSS software. The results of the study indicate that both taxpayer awareness and trust in the government have a positive and significant impact on taxpayer compliance in fulfilling their obligations to pay PBB. The conclusion of this study is that increasing public understanding and trust in the government can be an important factor in supporting improved tax compliance in the area.